2015
DOI: 10.1089/brain.2014.0285
|View full text |Cite
|
Sign up to set email alerts
|

Transcallosal Connectivity Changes from Infancy to Late Adulthood: An Ex Vivo Diffusion Spectrum Imaging Study of Macaque Brains

Abstract: Interhemispheric communication plays a critical role to ensure normal brain functions in cognition and behavior. Since non-human primate (NHP) brains resemble most aspects of the human brain, a thorough knowledge of interhemispheric cortical connectivity changes in NHP brains throughout the developmental and aging periods may provide valuable insights for translational and clinical research. In this study, formalin-fixed rhesus monkey brains aged from 1 to 24 years were utilized to examine transcallosal connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In contrast, the Poisson model considers different slopes in developing and aging periods and was able to capture asymmetric changes in diffusivity measurements over the lifespan 37 . Evolution pattern of DTI indices on brain maturation and aging has been found to adequately follow the Poisson regression model in both human and non-human primates’ brains 15 , 40 . As illustrated in Fig.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In contrast, the Poisson model considers different slopes in developing and aging periods and was able to capture asymmetric changes in diffusivity measurements over the lifespan 37 . Evolution pattern of DTI indices on brain maturation and aging has been found to adequately follow the Poisson regression model in both human and non-human primates’ brains 15 , 40 . As illustrated in Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Secondly, rodent early brain development differs greatly from primates, with greater immaturity at birth but more compressed maturation until adulthood, resulting in greater vulnerability that is not seen in humans, and/or exaggerate effects of genetic manipulation 11 , 12 . In contrast, nonhuman primates are similar to humans in anatomical structures and functional organizations and in their ontogenetic development 13 15 . Specifically, white matter fiber connections between striatum and prefrontal cortex or motor domains in primates are well established 16 .…”
Section: Introductionmentioning
confidence: 99%
“…However, previous diffusion tensor imaging studies of brain WM (44) and the optic nerve (45) of macaques showed age-related decreases in fractional anisotropy and increases in radial diffusivity. Another ex vivo diffusion spectrum imaging study (46) found that transcallosal connectivity declined in older macaques, which suggested that brain degeneration had occurred.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in the present study, significantly decreased FA at 48 h post occlusion was observed in the CC, fornix, IC, and EC in vehicle group, whereas no such FA changes were observered in CC and fornix in NRG-1 group, indicating NRG-1 protected CC and fornix white matter bundles from ischemia but not IC and EC. The CC is the largest commissural fiber system in the brain and places an essential role in interhemispheric commnuncation [55,56]. Also, its status may be associated with the degree of motor function and neurological deficit in stroke patients [57] and the gait function in the elderly [58].…”
Section: Discussionmentioning
confidence: 99%